Utilizing Palladium‐Stabilized Zwitterions for the Construction of N‐Heterocycles. Issue 56 (21st August 2017) - Allen, Benjamin D. W.; Lakeland, Christopher P.; Harrity, Joseph P. A.
Abstract: Pd catalysis provides a convenient method for the generation of zwitterionic intermediates that offer significant opportunities for the synthesis of functionalized heterocycles. The combination of electrophilic π‐allyl Pd fragments and C‐, N‐ and O‐centered nucleophiles allows these intermediates to react with readily available substrates to furnish a range of high value products with control of chemo‐, regio‐ and stereo‐selectivity. Abstract : Polar expedition ! Palladium catalysis offers access to a range of zwitterionic intermediates that permit significant opportunities for the synthesis of functionalized heterocycles. The combination of electrophilic π‐allyl Pd fragments and C‐, N‐ and O‐centered nucleophiles allows these intermediates to react with simple substrates to furnish a range of high value products with control of chemo‐, regio‐ and stereo‐selectivity.